(A Quasi-Experimental Study at the Tenth Grade Students of SMA Negeri 1 Cibeber) - Muhamad Ilham Hikmawandini; Nia Kurniawati (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2017)
THE USE OF NUMBERED HEADS TOGETHER TECHNIQUEIN TEACHING SIMPLE PAST TENSE   Muhamad Ilham HikmawandinyNia Kurniawati Abstract  The research was aimed at discovering whether Numbered Heads Together technique is effective to improve students’ ability in simple past tense and finding out the student’s responses toward this technique. The quasi-experimental design was utilized in order to collect the data. This quantitative research involved two classes of tenth grade at one senior high school in Cianjur in which one class was assigned as the experimental class and the other one was assigned as the control class. The instruments used were pre-test, post-test, and questionnaire attitudes towards the Numbered Heads Together technique. The pre-test was conducted in which the pre-test mean scores were the bases in identifying the initial learning framework of the participants. After conducting the selected lessons that employed the Numbered Heads Together technique in experimental class and employed Grammar Translation Method in control class, the students of both classes were given a post-test. The gain score of the two classes were compared by using Independent t-test. Results showed that the significance value was less than the significance level which was 0.032 < 0.05. It means that the Numbered Heads Together technique is effective to improve the students’ ability in simple past tense. Based on the questionnaire analysis, the findings showed that most of the students agreed that employing the Numbered Heads Together technique helps them to be more confident in term of participating because of group encouragement and benefits them to understand the hard concept of the learning material. Thus it can be concluded that the students’ responses toward the Numbered Heads Together technique were positive. Keywords: Numbered Heads Together, cooperative learning, simple past tense